Urgensi Pemilihan Auditor Eksternal: Antara Relevansi Leverage dan Biaya Audit Pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia - Bahtiar Effendi (Universitas Matana, 2021)
This study aims to analyze the effect of leverage and audit fees on the selection of external auditors in financial sector companies listed on the Indonesia Stock Exchange. The population of this research is all financial sector companies listed on the Indonesia Stock Exchange for the period 2016-2018. The samples were selected based on purposive sampling criteria with a quantitative method with a descriptive approach. Based on the purposive sampling method, obtained a sample of 38 companies with a total unit of analysis of 144 data obtained from 3 years of observation period. This study uses secondary data obtained from financial statement data and annual reports of publicly traded companies listed on the Indonesia Stock Exchange. By using logistic regression analysis as research data analysis, it is found that leverage has a negative and insignificant effect on the selection of external auditors. In addition, it was found that audit fees have a positive and significant effect on the selection of external auditors.